The contribution of "information science" to the social and ethical challenges of the information age [ - Baruchson-Arbib, Shifra (Bradford, England : Emerald, 2007)
This e-book explores the contribution of information science to social and ethical aspects of the information age such as: individual empowerment; education toward information awareness; information needs; the problem of decision making; manipulation of search result on the web; and the role of the information professionals in diminishing digital divide
1. Cover; CONTENTS; EDITORIAL BOARD -- 2. The contribution of "information science" to the social and ethical challenges of the information age -- 3. Current trends in library and information studies curricula around the world -- 4. An experiment to enhance awareness of the power of information -- 5. Knowledge in dialogue: empowerment and learning in public libraries -- 6. A model design proposal of a supportive web site for women experiencing IPV -- 7. Information professionals serving disadvantaged communities -- 8. Manipulating search engine algorithms: the case of Google -- 9. The health information specialist
Title from PDF cover (viewed Feb 13, 2008)
Includes bibliographical references
Keywords: Information science; Information society -- Moral and ethical aspects; Information technology -- Moral and ethical aspects; Information technology -- Social aspects